Proposed Musculoskeletal Examination of Youth and Adolescent Baseball Players. Issue 10 (October 2022) - Kindstrand, Nathan Allen; McNeill, Brian T.; Dickenson, Scott B.; Magnusson, Nick; Sum, Jonathan C.
Abstract: With a wide range of injuries in youth baseball, and more than 12 million amateur baseball players in the United States, a comprehensive list of tests and measures may be helpful to assess strength, mobility, and motor control throughout the kinetic chain to reduce risk of injury in this population. Many studies have looked at youth baseball players using a single test or a small number of tests to determine the prevalence of specific injuries in youth baseball, but to this author's knowledge, there is no comprehensive musculoskeletal screen published at this time specific to youth baseball. The purpose of this article is to review literature published over the last year relative to injury in youth and adolescent baseball players in an effort to update the reader on current concepts, risk factors in this population, and to provide an updated systematic screening process that may be used in reducing injury rates.